A novel saline-based occlusion tool allows for dye-less cryoballoon-based pulmonary vein isolation and fluoroscopy reduction - Rottner, Laura; Obergassel, Julius; Borof, Katrin; My, Ilaria; Moser, Fabian; Lemoine, Marc; Wenzel, Jan-Per; Kirchhof, Paulus; Ouyang, Feifan; Reissmann, Bruno; Metzner, Andreas; Rillig, Andreas (Frontiers in Cardiovascular Medicine, 2023)
Background Cryoballoon (CB)- based pulmonary vein isolation (PVI) remains guided by fluoroscopy and dye. The novel saline injection-based occlusion tool allows for pulmonary vein (PV)-occlusion assessment without the need for dye injection. Aim To compare KODEX-EPD guided CB-PVI using the novel saline injection-based workflow with conventional cryoablation for acute efficacy, fluoroscopy exposure and dye volume. Methods Consecutive atrial fibrillation (AF)- patients undergoing CB-PVI in conjunction with KODEX-EPD (CryoEPD group) were analyzed. Patients undergoing conventional CB-PVI (Cryo group) in the same time period acted as controls. Results One hundred forty patients [91/140 (65%) persistent AF] were studied. Seventy patients underwent CryoEPD procedures [64 ± 13 years, 21 (30%) female] and seventy patients underwent Cryo procedures [68 ± 10 years, 27 (39%) female]. A total of 560 PVs were identified and successfully isolated. Mean procedure time was 66 ± 15 min for the CryoEPD group, and 65 ± 19 min for the Cryo group (p = 0.3). Fluoroscopy time (CryoEPD 6 ± 4 min; Cryo 13 ± 6 min, p < 0.001) and dose area product (CryoEPD 193 [111; 297] cGycm2; Cryo 381 [268; 614] cGycm2, p < 0.001) were lower in patients undergoing CryoEPD compared with Cryo procedures. No dye was needed in the CryoEPD group while 53 ± 18 ml dye per patient were administered for the Cryo group (p < 0.001). The overall complication rate was comparable between both groups (p = 0.5). Conclusion KODEX-EPD guided AF-ablation enables dye-free CB-based PVI with reduced fluoroscopy exposure when compared to conventional CB-ablation, without differences in acute procedural outcomes or procedure duration.